Researching Digital Life : Orientations, Methods and Practice - Ash, James (SAGE Publications, Ltd. (UK), 2024)
We now live in a world where all aspects of everyday life are thoroughly mediated by digital technologies. Making sense of digital life is accordingly an essential undertaking for social science and humanities scholars. This multidisciplinary book provides an essential guide to researching digital life: Orienting readers with respect to methodologies, research design, and research ethics. Detailing key research methods, including interviews, surveys, ethnographies, walking methodologies, arts-based and participatory approaches, historical analysis, data visualisation, mapping and data analytics. Demonstrating these methods in action in real-world studies that have investigated apps and interfaces, social and locative media, mobilities, smart cities, and digital labour and work. The authors provide: • Non-Eurocentric perspectives and case studies from diverse disciplines  • Annotated further reading to help you situate your research alongside existing research in your field  • An outline of future directions for researching digital life. Accessible in style and richly illustrated, the chapters provide a wealth of key insights and practical information to ensure research projects are successfully planned and implemented.